IMPLEMENTATION OF CHANGE MANAGEMENT IN BUMDES: A CASE STUDY OF A FAMILY-BASED VILLAGE BUSINESS - Agus Rohmat Hidayat (Journal of Economic Development and Village Building, 2025)
In the era of economic disruption and digitalization, public sector organizations and local communities such as Village-Owned Enterprises (BUMDes) are faced with significant challenges in adopting change to remain relevant and competitive. This research aims to examine the implementation of change management in BUMDes that run family-based village businesses, focusing on adaptation strategies, leadership, community participation, and institutional structure. The case study was conducted on one of the BUMDes in Indonesia that has undergone structural and operational transformation after the COVID-19 pandemic. The research method used was descriptive qualitative with a case study approach, involving in-depth interviews, participatory observation, and document analysis. The results show that the success of change management is strongly influenced by the commitment of the village head, the involvement of family business actors, and community support. This research provides theoretical contributions in strengthening community-based change management models as well as practical benefits in the formulation of BUMDes development policies at the local level.